An exploration of women's groups as a tool of empowerment for Muslim women in South Africa. - Hassem, Zarina (My University, 2009)
This study examines the role women’s groups play in the lives of 10 Muslim women in South Africa. A qualitative methodology was employed to gain information from two women’s groups in Johannesburg. An open-ended questionnaire, focus groups, and individual interviews were used to elicit information. The data were initially analysed using a computer-based content analysis programme (Atlas-ti), to identify a priori and emergent themes and categories in the data. These themes and categories were then used as the basis for a qualitative interpretive analysis, focused in particular on issues of empowerment with respect to psychological, community, economic, intellectual and political empowerment, and more specifically on gender equality. The study would thus suggest that while these groups do have many positive outcomes, the issues dealt with in women’s groups cannot be isolated from the broader social context in which Muslim women live. While the processes of empowerment appear to have begun in areas of psychological, community, intellectual, economic and political empowerment in this sample of women, empowerment with respect to gender equality still seems far off.
Keywords: Community empowerment; Economic empowerment; Empowerment; Gender equality; Intellectual empowerment; Muslim women; Political empowerment; Psychological empowerment; Women's groups